Evaluation of in vitro anti-inflammatory potential of ethanolic extract of hybanthus enneaspermus - DR.S.UMAMAHESWARI; SINDHUJA KANNAN; K.S.SRIDEVI SANGEETHA (International Journal of Pharma and Bio Sciences, 2018)
The study was aimed to evaluate the in vitro anti-inflammatory activity of ethanolic extract of whole plant of Hybanthus enneaspermus. In vitro anti-inflammatory activity was estimated by human red blood cell membrane stabilisation (HRBC) method. The whole plant of Hybanthus enneaspermus was air dried and powdered. The powdered crude plant was cold macerated for 3 days with absolute ethanol, with occasional stirring.. The ethanolic extract of Hybanthus enneaspermus was analyzed in various concentrations as follows 50µg/ml, 100µg/ml, 200µg/ml, 400µg/ml and 800µg/ml. Diclofenac was used as standard anti-inflammatory drug. All the concentrations of Hybanthus enneaspermus ethanolic extract showed effective anti-inflammatory activity in a dose-dependent manner. It was found that the ethanolic extract of whole plant of Hybanthus enneaspermus at a concentration of 50µg/ml produced a percentage inhibition of 20.62% and in 100µg/ml it was increased to 29.88%. Likewise at 200µg/ml the percentage inhibition was 36.54%, which further increased to 56.72% at 400µg/ml. At 800µg/ml concentration it showed maximum inhibition of 69.90%. IC50 value of the extract was found to be 428µg/ml. The ethanolic extract of Hybanthus enneaspermusat a concentration of 800 µg/ml showed potent activity on comparing with the standard drug diclofenac sodium.